EVALUATION OF THE EPIDEMIOLOGY OF EXPOSED FRACTURES BEFORE AND DURING THE COVID-19 PANDEMIC - VINICIUS PAGLIARO FRANCO; GABRIEL MASSARICO GONÇALVES; ORLANDO COPETTI FRAÇÃO; HELOISA YUMI FUJIYA SUNGAILA; LUIZ FERNANDO COCCO; EIFFEL TSUYOSHI DOBASHI (Acta Ortopédica Brasileira, 2023)
ABSTRACT Objective: To assess the impact of the COVID-19 pandemic on the epidemiology and clinical outcomes of open fractures considering the periods before and during the pandemic. Methods: An observational and retrospective study, which included patients aged over 18 years, admitted to the Orthopedics and Traumatology Ward of Hospital São Paulo, of the Federal University of São Paulo (UNIFESP). Data was collected in two moments: pre-pandemic (March 1, 2019, to February 29, 2020) and during the pandemic (March 1, 2020, to February 28, 2021). Results: In total, 183 patients were evaluated with a mean age of 36 years ± 14 years. In the pre-pandemic period, 94 patients underwent surgery, 81 men (85.37%) and 13 women (14.2%), with a mean age of 36 ± 3 years. During the pandemic period, 89 patients were subjected to surgery, 77 men (86.6%) and 12 women (13.4%), with a mean age of 38 ± 3 years. Conclusion: During the pandemic, open fractures were still more common in men. Regarding hospital indicators, the prevalence of infections in the surgical wound and the length of stay of patients with open fractures increased, however, with little significance. Fractures classified as Gustilo IIIA were the most common, while the most common according to the AO classification were 33, 34, 42, 43, 2R3, and 2R3 + 2U2. The frequency of run overs during the pandemic decreased. However, firearm projectile injuries and falls and occupational injuries increased. Level of Evidence III, Retrospective Comparative Study.